2016
DOI: 10.1371/journal.pone.0150033
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Hypertension and Its Determinants in Patients with Concomitant Type 2 Diabetes Mellitus (T2DM) in Rural South Africa

Abstract: BackgroundPaucity of data on the prevalence, treatment and control of hypertension in individuals living with type 2 diabetes mellitus (T2DM) in the rural communities of South Africa may undermine efforts to reduce the morbidity and mortality associated with cardiovascular diseases. This study examines the socio-demographic and clinical determinants of uncontrolled hypertension among individuals living with T2DM in the rural communities of Mthatha, South Africa.MethodsThis cross-sectional study involved a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
90
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(118 citation statements)
references
References 42 publications
17
90
10
1
Order By: Relevance
“…14) Previous studies have reported that people with diabetes are less likely to have BP control. 15) Various results have been reported on the association between sex and BP control. In a study conducted in the United States, Dave et al 7) reported that male sex is positively associated with uncontrolled DBP in individuals taking antihypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…14) Previous studies have reported that people with diabetes are less likely to have BP control. 15) Various results have been reported on the association between sex and BP control. In a study conducted in the United States, Dave et al 7) reported that male sex is positively associated with uncontrolled DBP in individuals taking antihypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial proportion of people with T2DM have concomitant hypertension (20–60%, depending on age, sex, ethnicity and body mass index). Hypertension almost doubles the risk of all-cause mortality, and increases the risk of coronary artery disease threefold [6, 7]. In addition, hypertension enhances the progression of diabetic complications such as nephropathy, retinopathy and neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of African studies report a poor blood pressure control, ranging from 10% to 37% despite the high number of molecules often used. For example, in Dembélé' study in Mali involving 112 patients, almost half of the subjects were not well controlled under dual therapy [9], or Adeniyi et al, in South Africa who reported 76% of uncontrolled subjects while nearly three quarters of them were on triple therapy [27]. This rate is similar to the study, conducted in Portugal, and showed that only 40% of treated hypertensive patients with diabetes are really controlled [28].…”
Section: ) Study Of Risk Factors Open Journal Of Endocrine and Metabmentioning
confidence: 60%
“…A prospective study, conducted in Tunisia on 300 known and treated hypertensive patients type 2 diabetes (DT2), showed that only 23.3% of patients are really controlled on a blood pressure level [29]. This insufficiency of blood pressure control can be explained, by the observance estimated at only 15%, itself favored by the excessive costs of treatment and the complex care pathways [27].…”
Section: ) Study Of Risk Factors Open Journal Of Endocrine and Metabmentioning
confidence: 99%